The SVC additional adaptive voltage controller of isolated wind-diesel power system based on double sliding-mode optimal strategy - Mi, Yang (2020)
Due to the voltage fluctuation resulting from variable wind energy and reactive load change in an isolated wind-diesel hybrid system, an additional adaptive voltage compensation controller for static var compensator (SVC) by using double sliding-mode (SM) optimal strategy is proposed to maintain the system bus voltage stability. Considering the uncertainties of SVC model parameters and unobservable state variables, the SM algorithm is used to design the robust state observer and SVC adaptive voltage controller. The mathematical state model of isolated wind-diesel hybrid power system together with SVC is established, and then, the SM robust observer is constructed to estimate the SVC state variables. In order to improve the system bus voltage stability, an additional robust adaptive voltage controller is designed for SVC by selecting appropriate switching surface and adaptive reaching condition. The proposed control strategy is shown to be effective through opal-RT OP5600 simulator together with TIF28335 DSP for the isolated wind-diesel system under different operation point.